Overview of advanced structural and reliability techniques for optimum design of fixed offshore platforms - Onoufriou, Toula (My University, 1997)
The paper addresses the increasing use of advanced structural and reliability techniques in design optimisation affixed offshore platforms. Recent changes in regulatory and contract practices within the offshore industry coupled with developments in structural and reliability methods and increased hardware capacity create a suitable framework for increased design optimisation. The paper examines the current impact of advanced structural analysis techniques at component and system level and examines how recent developments in structural system reliability techniques are likely to affect the design process in future. Areas that need to be addressed before we are able to maximise the benefits from the use of these techniques are discussed together with recommendations for a more effective integration in the design process.
Keywords: Offshore structures; Reliability